A finding of potential coexisting bacteria and characterization of the bacterial communities in the fruiting body of Sarcodon aspratus - Chen, Fu-Chia; Chen, Fu-Chieh; Motoda, Taichi (Folia microbiologica, 2024)
Sarcodon aspratus (Berk.) S. Ito is a Japanese local dish with unique aroma and is effective against allergic diseases. However, its cultivation was still difficult. Recently, coexisting bacteria were regarded as an important factor for mycelium growth and fruiting body formation. Therefore, we performed 16S rRNA amplicon sequencing in the fruiting body of S. aspratus and its adhered soil to understand the bacterial communities in the fruiting body of S. aspratus. The fruiting body group showed lower alpha diversities and a significant difference in the structure of bacterial communities compared to the soil group. In addition, Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium had the highest relative abundance in the fruiting body group, and it was also a potential coexisting bacterium in the fruiting body of S. aspratus by linear discriminant analysis effect size (LEfSe) analysis. This highest relative abundance phenomenon in Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium clade was also found in the fruiting body of Cantharellus cibarius. These findings suggested that Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium plays a key role in the bacterial communities in the fruiting body of S. aspratus. Bacteria in the fruit bodies of S. aspratus and C. cibarius probably present a similar coexistence model.
Keywords: fylogeneze; DNA bakterií; biodiverzita; Fruiting Bodies, Fungal; Soil Microbiology; Biodiversity; RNA, Ribosomal, 16S; Sequence Analysis, DNA; mikrobiota; Bacteria; plodnice hub; půdní mikrobiologie; Phylogeny; DNA, Bacterial; Microbiota; sekvenční analýza DNA; RNA ribozomální 16S